POLA KEBIASAAN MAKAN ORANG LANJUT USIA (Studi Kasus: Penderita Penyakit Hipertensi Sukubangsa Minangkabau di Jakarta) - Fitriani, Erda (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
Food is a basic biological need for humans to stay alive, and now food has beenlinked to culture. Not all types of food available in the environment are considered asfood. Patterns of eating habits ingrained from childhood will take effect later in olderage. This article explains the eating habits of the elderly people of Minangkabau whosuffer from hypertension. The result shows that the culture greatly affects the patterns ofeating habits of the elderly. The eating habit happens to be one of the factors causinghypertension. After suffering from hypertension, the elderly are also difficult to changeeating habits.Key words: eating habits, elderly, culture